England under the Stuarts - Trevelyan, George Macaulay, 1876-1962, author.
1 online resource (xxvi, 583 pages)
Keywords: 'While Germany boasts her Reformation and France her Revolution, England can point to her dealings with the House of Stuart.' - G.M. Trevelyan, from the Introduction England Under the Stuarts is an outstanding and highly engaging account of English history in the years between 1603 and 1714, charting England's path from nation to empire. G. M. Trevelyan's masterful narrative explores the major events of this period, which witnessed the upheavals of the Civil War, the Restoration and the Glorious Revolution. While never neglecting to examine the social, economic and religious conditions of English life, Trevelyan highlights the epic struggle between the threats of absolutism and despotism and the staunch political liberty and toleration that emerged during these years. He also gives the reader a vivid sense of what it was like to be there at the time, conveying a rich and dramatic flavour of events. As such, England Under the Stuarts remains certain to inform and delight anybody with an interest in this period of English history. This Routledge Classics edition includes a new Foreword by Peter Gaunt.